Optimization of hygromycin concentration as a selectable marker to select putative transformants of HD3090 wheat cultivar transformed using mature seeds via in planta method - Namrata Pandey; R.M. Mishra; Sharmistha Barthakur (Annals of Agricultural Research, 2023)
Hygromycin is commonly used to identify and maintain prokaryotic and eukaryotic cultured cells that carry the hygromycin resistance gene. In plant research, the hygromycin phosphotransferase (HPTII) resistance gene is commonly utilized as a selectable marker. In Agrobacterium-mediated transformation systems it is used at a concentration ranging from 10 mg/L to 75 mg/L depending on different crops and tissues used as explants. The higher concentration of hygromycin is harmful to non-transformed explants. The response to antibiotics and transformation is also genotype-specific in wheat as observed from the literature. Thus for effective optimization and selection of transformants, we compared the growth of transformed and untransformed plants utilizing a range of hygromycin concentrations vide seed germination analysis towards optimization for application in segregation analysis of transformed plant selection. The 50 mg/L concentration of hygromycin was optimized to be used for the selection of cvHD3090 wheat transformants which were transformed using apical meristem tissue of germinating seeds.